2008
DOI: 10.1007/s10620-008-0478-5
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Decreases the Duration of Postoperative Ileus After Abdominal Surgery: An Experimental Study of Conscious Dogs

Abstract: Postoperative ileus (POI) is a transient bowel dysmotility that occurs following many types of operations and is one of the most common complications of gastrointestinal surgery. We hypothesized that enteral supplementation of glutamine after abdominal surgery would restore fuel to the small intestine, suppress oxidative stress, and lead to improvement in POI. Twelve dogs underwent distal gastrectomy and were each randomly assigned to one of two groups based on postoperative treatment: the water injection (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Furthermore, we first reported the effect of glutamine on gastrointestinal motor activity after gastrectomy in humans. The present study shows that plasma glutamine levels decrease after surgery, a finding that is in agreement with previous reports [11,13]. The glutamine group in this study showed a smaller decrease in mean plasma glutamine level and higher gastrointestinal motor activity after gastrectomy than the control group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, we first reported the effect of glutamine on gastrointestinal motor activity after gastrectomy in humans. The present study shows that plasma glutamine levels decrease after surgery, a finding that is in agreement with previous reports [11,13]. The glutamine group in this study showed a smaller decrease in mean plasma glutamine level and higher gastrointestinal motor activity after gastrectomy than the control group.…”
Section: Discussionsupporting
confidence: 93%
“…Gut glutamine requirements are increased during critical illness; a number of studies suggest that glutamine may be essential for the maintenance of gut metabolism, structure, and function [4,6]. We previously reported that glutamine improved gastrointestinal motor activity after gastrectomy and decreased the duration of postoperative ileus in the dog [11].…”
Section: Discussionmentioning
confidence: 93%
“…Critically ill patients were shown to profit from systemic antioxidants [44], and some studies suggest a detrimental role for oxidative stress in intestinal postoperative or septic intestinal dysfunction [37,45,46]. However, the results within our ex vivo endotoxemia model demonstrate that the antiinflammatory effect of Omegaven occurs also in the absence of vitamin E during the inflammatory stimulus.…”
Section: Discussionmentioning
confidence: 70%
“…Glutamine supplementation has been shown to prevent chemotherapy-induced diarrhea ( 23 ). Using animal experiments with dogs, Ohno et al reported that glutamine improved intestinal obstruction after abdominal surgery ( 24 ). Additionally, Ohno et al ( 25 ) reported that glutamine supplementation improved the decrease in plasma glutamine levels and gastrointestinal motility after gastrectomy.…”
Section: Discussionmentioning
confidence: 99%